The study of pile capacity for buildings in UiTM Penang / Budi Iskandar Ibrahim - Ibrahim, Budi iskandar (Faculty of Civil Engineering, 2006)
Pile is one of many solutions in foundation engineering practice. Places such as coastal area of peninsular Malaysia which consists of very deep soft clay and highly compressible soil, are suitable solution for building supported on pile. In designing pile, there are 2 important parameters that influence and affect the pile capacity. They are the base resistance, and skin friction. For this research, these parameters will be counted in order to compare the different methods of finding pile capacity. In this study, three methods in determining pile capacity are used namely Chin Method, Meyerhof Method and Hiley Formula. These 3 methods will be compared to locate the differences and advantages and later finding the most accurate method to determine pile capacity. The pile capacity includes the ultimate bearing capacity and allowable bearing capacity of the pile